Neurofilament light predicts decline in attention but not episodic memory in preclinical Alzheimer disease - Aschenbrenner, Andrew J. (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrospinal fluid tau and neurofilament light (NfL) are two biomarkers of neurodegeneration in Alzheimer disease. Previous reports have shown that the influence of tau on cognitive decline depends on levels of amyloid burden whereas NfL predicts decline independently of amyloid. Most studies use a global cognitive composite as the primary outcome, and it is unknown if critical cognitive domain scores are similarly sensitive to rates of decline due to neurodegeneration. OBJECTIVE: To examine the unique contribution of amyloid, tau and NfL to rates of cognitive decline in multiple cognitive composites in a cognitively healthy, middle-aged to older adult cohort. METHODS: A total of 255 participants (55% female; mean age = 66.2 years, range = 42.5 – 86.7 years) completed CSF studies and serial cognitive assessments to measure global cognition, episodic memory and attentional control. Linear mixed effects models were used to examine rates of change on each composite score as a function of baseline biomarker levels. RESULTS: Total tau predicted decline in attention regardless of amyloid status, but the relationship to global cognition and episodic memory was dependent on amyloid, replicating prior literature. NfL predicted decline in attention and global cognition, but not memory, and this effect was independent of amyloid status. CONCLUSIONS: These findings suggest that NfL can be used to monitor cognitive decline in aging and Alzheimer disease and that an attentional control composite may be a better outcome for tracking general neurodegenerative effects on cognition.